The impact of ESG performance on firms’ technological innovation: evidence from China - Zhang, Xiaoyun; Li, Wenjun; Ji, Tonghui; Xie, Huimin (Frontiers in Environmental Science, 2024)
This article examines the impact of ESG performance on firms' technological advancement and investigates its operational mechanisms by utilizing statistical data obtained from Chinese A-share listed enterprises spanning the period from 2011 to 2021. It is discovered that strong ESG performance substantially enhances corporate technological innovation. Corporate ESG performance promotes technological innovation by means of external mechanisms, which include enhancing corporate network location and increasing institutional shareholding. Internal mechanisms, such as reducing labor costs and easing financing constraints, also promote corporate technological innovation. The influence of ESG performance on corporations exhibits heterogeneity, with a notable effect observed in stimulating innovation specifically among labor-intensive firms, non-state-owned enterprises, those operating in highly competitive industries, and the mature enterprises. The research outcomes are valuable in hastening the adoption of ESG tactics by international organizations, boosting their effectiveness in the marketplace and fostering sustainable development.